Do Audit Committees Improve Financial Perfomance? Evidence from Basic Materials Companies in Indonesia - Silkfan, Rara; Fito Cahya Putra; Khairul Akbar; Adryan Jabbar Pasha; Syafira Riyanda Rahmania (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2026)
This study examines the effect of audit committee characteristics on the financial performance of basic materials companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Using a quantitative approach with panel data regression on 210 firm-year observations, this study analyzes the role of audit committee independence, financial expertise, meeting frequency, and size in influencing firm performance, measured by return on assets (ROA). The results reveal that audit committee independence, financial expertise, and meeting frequency have a positive and significant effect on financial performance, indicating that effective monitoring and oversight contribute to improved profitability. In contrast, audit committee size does not show a significant impact, suggesting that governance effectiveness is not determined by the number of members but by their competence and independence. These findings highlight the importance of strengthening qualitative aspects of audit committees to enhance transparency, reduce agency conflicts, and support sustainable financial performance, particularly in emerging market contexts.